The impact of accent stigma on self-efficacy and acculturation strategy among international students in the United States - Yan, Xiaodi (Frontiers in Psychology, 2024)
This paper aimed to understand international students’ experience of accent stigma during interpersonal interactions, and how it affected their self-efficacy and acculturation strategy during intercultural adjustment. Study 1 conducted in-depth interviews with international students, and identified verbal disapproval, verbal avoidance, nonverbal disapproval, and nonverbal avoidance as four behavioral markers that signal the enactment of accent stigma during interpersonal interactions. Study 2 distributed a survey to international students with scales measuring perceived accent stigma, perceived discrimination, perceived hate, fear, self-efficacy, and integration into the host culture. Study 2 found that perceived accent stigma was associated with more perceived discrimination, perceived hate, and fear. Perceived accent stigma also had negative impacts on self-efficacy, which in turn, resulted in poor integration into the host culture. These findings had important theoretical and practical implications in terms of how to better support and serve international students during their stressful transitional period in a new culture.